AN ANALYSIS OF EXPERIENTIAL AND TEXTUAL MEANING OF KELAMBU NYAWA TEXT - Suliadi, S (Warmadewa University, 2017)
Representation of experiential meaning, textual meaning, and general ideology realized in Mosquito Net text are problem in this research. It is aimed at investigating representation of experiential meaning, textual meaning, and general ideology in Kelambu Nyawa Text text are problem in this research and describing the relevance of the research result to learning discourse in higher education. It was conducted by using qualitative-quantitative descriptive (mixed-method). In collecting data, observation, interview, document and note-taking method were employed. Data analysis carried on with the orientation of formal and informal methods. The results showed that the dominant process found in the text of Mosquito Nets is a material process consisting of 115 (35.50%). The use participants in the text is dominated by participant I (Netting Lives) consisting of 308 participants or 33.44%, participant II consists of 264 consisting of 85 or 33.20%, other participant consists of 24 dominated by Reach taking over 15 times (62.25%). Furthermore, the use of circumstance in the text of Kelambu Nyawa is dominated by circumstantial environment, which were used over 51 times (26.42%). The dominant theme used in of Mosquito Nets text topical theme. It was used 146 times (48.18%). Furthermore, the ideology realized in the text of Mosquito Net is the belief of the Sufism in God as the source of everything. The relevance of this research to discourse learning at universities is to the extent that the results of this research can be used as reference to analyzing written text, especially on the transitivity and theme rhema system by using Systemic Functional Linguistics theory (SFL).